The Assessment of CDX1, IHH, SHH, GATA4, FOXA2, FOXF1 in Congenital Intra-Abdominal Adhesions - Freijere Pope, Helēna; Pilmane, Māra; Junga, Anna; Pētersons, Aigars (Acta medica Lituanica, 2024)
Congenital abdominal adhesions are a rare condition that can result in a small bowel obstruction at any age, more frequently in pediatric populations. The cause remains unknown, and the importance of aberrant congenital bands is related to the difficulty of diagnosis, and cases of death with late detection have been documented. This research examines the expression of Caudal Type Homeobox 1 (CDX1), Indian Hedgehog (IHH), Sonic Hedgehog (SHH), GATA Binding Protein 4 (GATA4), Forkhead Box A2 (FOXA2) and Forkhead Box F1 (FOXF1) gene expression in human abdominal congenital adhesion fibroblast and endothelium cells by chromogenic in situ hybridization, with the aim of elucidating their potential association with the etiology of congenital intra-abdominal adhesion band development. The potential genes’ signals were examined using a semi-quantitative approach. Significant correlations were observed between the expression of CDX1 (p <.001) and SHH (p=0.032) genes in fibroblasts from congenital intra-abdominal adhesions compared to fibroblasts from control peritoneal tissue. Statistically significant very strong correlations were found between the CDX1 and IHH comparing endothelium and fibroblast cells in congenital abdominal adhesion bands. There was no statistically significant difference found in the distribution of IHH, FOXA2, GATA4, and FOXF1 between the fibroblasts and endothelium of the patients compared to the control group. The presence of notable distinctions and diverse associations suggests the potential involvement of numerous morpho-pathogenetic processes in the development of intraabdominal adhesions.